Applied signal and image processing : multidisciplinary advancements - Qahwaji, Rami, 1972-; Green, Roger, 1951-; Hines, Evor, 1957- (Information Science Reference, 2011)
"This book highlights the growing multidisciplinary nature of signal and image processing by focusing on emerging applications and recent advances in well-established fields, covering state-or-the-art applications in both signal and image processing, which include optical communication and sensing, wireless communication management, face recognition and facial imaging, solar imaging and feature detection, fractal analysis, and video processing"--